Cryptosporidiosis in HIV seropositive patients in Kasturba Hospital, Manipal, Karnataka, South India - Singh, A.; Bairy, I. (Journal of Institute of Medicine Nepal, 2007)
Background: Cryptosporidium parvum a coccidian protozoal parasite causes a protracted life threatening diarrhea in HIV sero-positive patients. This study was conducted to find out distribution of cryptosporidium infection in HIV sero-positive patients (with acute or chronic diarrhea) admitted in Kasturba Hospital, Manipal, South India. Method: Freshly passed stool samples were collected and stained with modified Ziehl Neelson staining technique and examined under microscope for the detection of oocyst of Cryptosporidium. Results: Thirty out of 70 (42.85%) of HIV sero-positive patients were found to have Cryptosporidium parvum oocyst in their stool samples . Conclusion: Known prevalence of cryptosporidial in HIV positive patients can help in starting prophylaxis and can significantly reduce morbidity and mortality associated with severe diarrhea. Journal of Institute of Medicine Vol.27(2) 2005